Etiología y curso clínico de la neutropenia febril en pacientes pediátricos tratados en el Hospital Infantil de Morelia - Correa García, Arturo (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
Pediatric cancer is the leading cause of death due to illness in children in Mexico. Currently the cure rate in developed countries reaches 80%, it has been identified that the presence of fever and neutropenia is an important cause of morbidity and mortality. It constitutes a real urgency, given that the possibility of septic shock and death is high, and it is necessary to carry out a rapid evaluation and establishment of the treatment. The characteristics and clinical course of patients with fever and neutropenia in Mexico are unknown, since most of the literature is published abroad. It is considered that 10 to 50% of solid tumors and 80% of hematological malignancies present an episode of febrile neutropenia during their chemotherapy treatment with a mortality that varies between 4 and 30%. OBJECTIVES: To analyze the etiology and clinical course of children with fever and neutropenia treated at the Children's Hospital of Morelia. Estimate the frequency of febrile neutropenia by age, sex and place of residence. Know the type of cancer most frequently affected with fever and neutropenia. Recognize the predictive factors to develop sepsis in patients with fever and neutropenia. MATERIAL AND METHODS: Descriptive, transversal, observational, retrospective, without risk. Universe of study: all oncological patients who presented a diagnosis of fever and neutropenia under treatment at the Children's Hospital of Morelia "Eva Sámano de López Mateos" from January 1, 2016 to December 31, 2016.

El cáncer pediátrico es la primera causa de muerte por enfermedad en niños en México. Actualmente la tasa de curación en países desarrollados alcanza el 80%, se ha identificado que la presencia de fiebre y neutropenia es una causa importante de morbimortalidad. Constituye una verdadera urgencia, dado que la posibilidad de choque séptico y muerte es alta, siendo necesario realizar una rápida evaluación e instauración del tratamiento. Se desconoce con precisión las características y el curso clínico de los pacientes con fiebre y neutropenia en México ya que la mayoría de la literatura se publica en el extranjero. Se considera que del 10 a 50% de los tumores sólidos y 80% de las neoplasias hematológicas presentaran un episodio de neutropenia febril durante su tratamiento quimioterapéutico con una mortalidad que varía entre 4 y 30%. OBJETIVOS: Analizar la etiología y el curso clínico de los niños con fiebre y neutropenia atendidos en el Hospital Infantil de Morelia. Estimar la frecuencia de neutropenia febril por edad, sexo y lugar de residencia. Identificar el tipo de cáncer más frecuentemente afectado con fiebre y neutropenia. Reconocer los factores predictivos para desarrollar sepsis en pacientes con fiebre y neutropenia. MATERIAL Y METODOS: Descriptivo, transversal, observacional, retrospectivo, sin riesgo. Universo de estudio: todos los pacientes oncológicos que presentaron diagnóstico de fiebre y neutropenia en tratamiento en el Hospital Infantil de Morelia "Eva Sámano de López Mateos" del 1 enero de 2016 a 31 diciembre de 2016.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Pediatría
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4288; info:eu-repo/classification/cti/3; FCMB-E-2018-0106; Curso clínico; Factores de sepsis; Cáncer